About the optimal numerical solution of the Navier-Stokes equations in the "vortex-current" system (Eurasian Research Bulletin, 2024)
For numerical simulation of the Navier-Stokes equations in the "vortex-current" system, the Peaceman-Reckford scheme is used in combination with an iterative alternating direction scheme with optimal iterative parameters. The efficiency and high accuracy of the applied numerical method are illustrated.